Bladder augmentation in rabbits with anionic collagen membrane, with or without urotelial preservation. Cistometric and hystologic evaluation - Lepper, Fábio G. O. [UNESP]; Ramos, Tamara M.; Trindade Filho, José C. S.; Vale, Fabiana R.; Padovani, Carlos R.; Goissis, Gilberto (International Braz J Urol : Official Journal Of The Brazilian Society Of Urology, 2002)
The use of bowel segments to perform bladder augmentation is associated with several metabolic and surgical complications. A great variety of synthetic materials, biodegradable or not, have been tested. Collagen-based biomaterials have shown effectiveness for the regeneration and obtainment of a functional bladder. Assess the functional and histological response of the rabbit bladder to anionic collagen membrane (ACM), either when it is anastomosed to the bladder or it is placed onto bladder after vesicomyectomy. In 15 male rabbit a partial cystectomy was performed. After 4 weeks they were divided in 3 groups. Group 1 (G1) - bladder augmentation with ACM. Group 2 (G2) ACM is placed onto bladder after vesicomyectomy. Group 3 (G3) control group. Maximal bladder capacity (MBC) and weight were assessed with 4 (M1), 8 (M2) and 12 (M3) weeks after partial cystectomy. In M3 was performed the sacrifice and extraction of the bladder and kidneys for anatomopathologic study. There were neither bladder stones, nor implant extrusion in M3. There was a significant increase in MBC in G1 and G2 (p<0.05), but no statistical differences in G3 (p=0.35). There is no significant difference comparing G1 and G2. In M3, both groups have shown a bigger MBC than G3 (p<0.05). The microscopic assessment showed an inflammatory reaction in the bladder augmented, with urothelium preserved. The ACM was effective for the increase of MBC. The bladders with preservation of the urothelium have shown an extensive inflammatory process.
Keywords: Bladder; Transplant; Collagen; Rabbit model; Urodynamics